2002
DOI: 10.1016/s0269-7491(02)00160-4
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamide preparations for protection of water quality threatened by agricultural runoff contaminants

Abstract: "Capsule": Polyacrylamide preparations show promise in reducing flow of sediments, nutrients and microorganisms from animal production facilities. AbstractWaste streams associated with a variety of agricultural runoff sources are major contributors of nutrients, pesticides and enteric microorganisms to surface and ground waters. Water soluble anionic polyacrylamide (PAM) was found to be a highly effective erosion-preventing and infiltration-enhancing polymer, when applied at rates of 1-10 g m-3 in furrow irrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 59 publications
(66 reference statements)
2
41
0
4
Order By: Relevance
“…In the experiment, PAM was considered to be a comparison with LSAA. The results indicated that PAM could significantly reduce the output of runoff, TSS, COD Cr , TN, and TP (Tables 2-6), which was consistent with the conclusion of many correlative studies (Lenze and Sojka, 1994;Lentz et al, 1998;Entry et al, 2002). The data of the comparison between LSAA and PAM indicated no significant difference.…”
Section: Comparison Between Lsaa and Pamsupporting
confidence: 86%
See 1 more Smart Citation
“…In the experiment, PAM was considered to be a comparison with LSAA. The results indicated that PAM could significantly reduce the output of runoff, TSS, COD Cr , TN, and TP (Tables 2-6), which was consistent with the conclusion of many correlative studies (Lenze and Sojka, 1994;Lentz et al, 1998;Entry et al, 2002). The data of the comparison between LSAA and PAM indicated no significant difference.…”
Section: Comparison Between Lsaa and Pamsupporting
confidence: 86%
“…The application of polymers on reducing surface runoff contamination was proved to be a feasible way to control NPS. From the early 1990s, polyacrylamide (PAM) was used as an effective strategy to control soil erosion (Lentz and Sojka, 1994) and to protect water quality threatened by agricultural runoff contaminations (Entry et al, 2002). The successful use of PAM drove the development of the polymers with * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The treatments with more concentrated solution in our study decreased emergence compared to the control, Figure 1. We observed that the 18 and 37% 8102 solutions formed a crust or polymer mat on the soil surface (Entry et al, 2002), possibly by cementing surface aggregates to one another. The less concentrated 5% 8102 solution appeared to stabilize individual aggregates without forming a polymer mat.…”
Section: Laboratory Studymentioning
confidence: 81%
“…For example, PAM prevents yearly topsoil runoff of up to 15.8 t ha -1 (Lenz and Sojka 1994) and at least three times that as on-field erosion. In addition to preventing herbicide and pesticide toss, PAM was recently shown to sequester biological and chemical contaminants of runoff, providing significant potential for reduced spread of phytopathogens, animal coliforms, and other toxic organisms Sojka 2000, 2003;Entry et al 2002.…”
Section: Environmental Impact Of Pam-alternatives To Pammentioning
confidence: 99%